171 Impact of Baseline Cervical Mal-Alignments on Proximal Junctional Kyphosis Following Thoraco-lumbar Corrective Surgery. (1st April 2022) - Passias, Peter G.; Passfall, Lara; Lafage, Virginie; Lafage, Renaud; Smith, Justin S.; Line, Breton G.; Tretiakov, BSME; Peter; Protopsaltis, Themistocles; Daniels, Alan H.; Kebaish, Khaled; Gum, Jeffrey L.; Koller, Heiko; et al.
Abstract : INTRODUCTION: The regions of the spine are often referred to a chain of correlation, where malalignment in one aspect may cause compensatory changes in another area of the spine or lower extremities. METHODS: Included: operative ASD patients (Coronal Cobb = 20°, SVA = 50 mm, PT = 25°, or TK > 60°) >18 yrs with concurrent cervical deformity (C2-C7 kyphosis <-15°, TS-CL > 35°, cSVA > 4 cm, CBVA > 25°, McGregor's slope >20°, or C2-T1 kyphosis >15° across any 3 vertebra). Patients with UIV above T1 or with preop PJK were excluded. Patients were grouped according to three deformity classification schemes: Ames CD modifiers, Kim et al. sagittal morphotypes, and Mizutani et al. head-trunk balance. Univariate analyses and logistic regression assessed the impact of these three deformity classifications on PJK and PJF rates by 2Y postop. RESULTS: 708 patients with concurrent ASD and CD included (62 yrs, 71% F, 28.2 kg/m 2, levels fused 10.1 ± 4.5). Sagittal morphotypes [flatneck(FN), focal deformity(FD) and cervicothoracic(CT)] were identified based on radiographic thresholds adapted from Virk et al.: 18 pts(2.5%) FN, 10(1.4%) FD, and 206(29.1%) were CT. Head-balance[HBal] was defined as SVA < 0, LL > PI, T1S < 20°, while trunk-balance[TBal] was SVA > 0, LL < PI, T1S > 20°. 14(2.0%) were HBal and 474(66.9%) were TBal. By Ames CD modifiers, the following had high deformity: cSVA 0%, TS-CL 45.6%, SVA 43.8%, and Horiz 21.8%. Overall, 301 pts (42.5%) developed PJK by by 2Y, and 73 pts (10.3%) had PJF. Regression analysis identified CD classification groups that were predictors of PJF: FD morphotype(OR: 7.6) and high Ames SVA deformity (OR: 1.8); both p < 0.05. These increased odds of PJF remained when controlling for use of PJK prophylaxis during index surgery. CONCLUSION: In patients with concurrent cervical and thoracolumbar deformities undergoing isolated thoracolumbar correction, the use of existing cervical deformity classification schemes can allow for preoperative assessment of PJK and PJF risk. Speficially, high deformity by Ames criteria and focal deformity morphotype had increased odds of PJF despite prophylaxis.